Discovery and characterisation of field resistance to organophosphorus chemicals in a major mite pest, Halotydeus destructor. Issue 8 (7th February 2017) - Umina, Paul A; Lord, Alan; Micic, Svetlana; Edwards, Owain
Abstract: BACKGROUND: The redlegged earth mite ( Halotydeus destructor ) is an agricultural pest in Australia that attacks a wide variety of crops and pasture species. Chemicals remain an important part of control strategies for H. destructor, despite the existence of resistance to pyrethroid insecticides in this species. Recent chemical control failures involving a second insecticide class, organophosphates, were investigated using pesticide bioassays. RESULTS: We confirmed, for the first time, resistance to organophosphates in H. destructor, and show that resistance is not confined to a single property, or region. There was no evidence that resistance to organophosphorus chemicals has evolved in Australian states outside of Western Australia. CONCLUSION: These findings demonstrate the strong evolutionary capability of H. destructor and highlight the need for ongoing resistance surveillance within Australia. © 2017 Society of Chemical Industry